Revolution and counter-revolution in Spain : including "The Civil War in Spain" - Morrow, Felix (New York : Pathfinder Press, 1974)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Spaanse Burgeroorlog; revoluties; Spanje